Be Real, Do Not Be Fake: A Pilot Study on Universiti Sains Islam Malaysia Students' Fake News Literacy - Kamarulbaid, Afiqah Mior; Mohd Sofian, Muhammad Raqib; Abu Hasan, Nurul Nadirah; Mohd Noor Shah, Nurul Fathihin; Mustaffa, Norsimaa; Mohamed Najid, Hafizuddin; Mhd Omar, Mohd Faridh Hafez (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
If nothing is accomplished to stop it, the virality of fake news on social media will continue to grow and become more damaging, particularly among young people. Recognizing false information and verifying sources has become increasingly important as people rely on the Internet and social media for their news. The primary objective of this study is to assess the level of understanding of fake news media literacy among university students. Forty-three Universiti Sains Islam Malaysia students enrolled in the New Media Communication program were polled for this research. This study uses descriptive statistics to analyze the data collected via Google Forms—the results of examining the data generated immediately through a Google form. Young people read the news online but still have limited media literacy when assessing the truth of information. Research suggests that false statement is commonly discovered because young people do not carefully examine online news. Researchers conduct in-depth interviews and studies with this demographic to better understand how young people process information and evaluate its veracity. This research adds to the expanding body of knowledge on student use of social media in Malaysia, especially on how students get their news in light of the results of this pilot study, the main research project will consist of in-depth interviews with students to understand more about their perspectives on how to identify and differentiate between real and fake news.